Improvement of Power Generation Facility Investment Systems for Achieving Resource Adequacy in Electric Power Industry - Suil Lee (Korea Development Institute (KDI), 2015)
- Investment in power generation facilities in Korea is planned and implemented in accordance with the Basic Plan on Electricity Demand and Supply, which involves the following problems: - Problem 1: An underestimation of long-term electricity demand due to optimistic projections on electricity price results in insufficient investment in power generation facilities. - Problem 2: Uncoordinated investment plans in power generation facilities and transmission networks can exacerbate regional disproportion of power facility distribution and can cause inefficiency and instability in transmission networks. - Problem 3: Leaving the assessment of uncertainty factors up to the small group who lead the planning may distort future power generation mix. - Problem 4: A considerable number of the planned investment projects remain unexecuted due to the absence of effective means to enforce or induce implementation of investment plans - This paper attempts to propose deregulation of power generation market entry and introduction of a capacity obligation scheme as measures to deal with Problems 3 and 4. - The efforts to handle Problems 1 and 2 is not addressed in this paper, as there were efforts to resolve these concerns in the Sixth Basic Plan on Electricity Demand and Supply in 2012. - Uncertainty factors affecting the economic feasibility and environmental performance of power generation facilities vary by energy source. In the case of coal- and LNG-fired power generation, the possibility for distortion within the power generation mix can be minimized by lowering the barriers to market entry. This can be achieved by offering more autonomy to power producers in assessing future uncertainty factors. - Uncertainties over investment in power generation facilities can be minimized via a contract between power producers and suppliers, arranged through the introduction of a capacity obligation scheme. In such a scheme, obligation is imposed upon the power supplier (KEPCO in Korea) to secure power capacity that can ensure a stable supply to meet future demand for electricity.
Keywords: 330